Seawater carbonate chemistry and activity, escape response, and muscle physiology of marine threespine stickleback (Gasterosteus aculeatus) - Yoon, Gwangseok R; Khodikian, Elissa; Ren, Gary J; Porteus, Cosima S (PANGAEA, 2025)
We exposed threespine stickleback (Gasterosteus aculeatus) to pCO2 of ~ 700 µatm (pH 7.9 representing current levels), ~ 1400 µatm (pH 7.6 representing upwelling events) and ~ 3500 µatm (pH 7.3 representing a future predicted scenario for coastal areas) for 2 weeks. We evaluated the baseline activity, interindividual distance as a proxy for group sociality, and escape response. Then, we measured whole-body routine metabolic rate and maximum metabolic rate to determine if changes in locomotory traits might be due to changes in metabolism. We also assessed lactate dehydrogenase (LDH; EC 1.1.1.27), which is a glycolytic enzyme that interconverts pyruvate and NADH to lactate and NAD+ as well as citrate synthase (CS; EC 2.3.3.1), which is a mitochondrial enzyme that catalyzes the first step of TCA cycle to synthesize citrate from acetyl-CoA and oxaloacetate. Additionally, we also measured muscle fiber size and succinate dehydrogenase staining as a measure of muscular metabolism. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Figshare (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-16.
Keywords: Animalia; Behaviour; Chordata; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Gasterosteus aculeatus; Growth/Morphology; Laboratory experiment; Nekton; North Pacific; Other metabolic rates; Other studied parameter or process; Pelagos; Respiration; Single species; Temperate